2003
DOI: 10.1007/bf03220179
|View full text |Cite
|
Sign up to set email alerts
|

In vivo metabolism of N-phenyl-N′-(3,5-dimethylpyrazole-4-yl) thiourea in rats

Abstract: Thiourea derivatives have been shown to posses several biological activities. Therefore a series of N-substituted -N'-(3,5-di/1,3,5trimethylpyrazole-4-yl)thioureas were synthesized and the antitubercular and anticonvulsant activities were studied. Among the new compounds, N-phenyl-N'-(3,5-dimethylpyrazole4-yl)thiourea (S) was demonstrated to have remarkable anticonvulsant activity. In this study, S was selected as a model compound and the in vivo metabolic pathway in rats was investigated. The substrate was gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
0
10
0
Order By: Relevance
“…General procedure for the preparation of NSubstituted-N'-(3,S-di/I,3,S-trimethylpyrazole-4-yl)thioureas (TI-T3) The intermediate products 4-amino-3,5-dime-thyVl, 3,5-trimethylpyrazole were prepared in 4 stages from aniline or ethyl 4-aminobenzoate according to the reported procedures (19). The intermedi-ate products (0.0085 mol in 100 ml anhydrous acetone) underwent reaction with appropriate isothio-cyanate (0.0085 mol) in anhydrous acetone (100 ml).…”
Section: Chemicalsmentioning
confidence: 99%
See 1 more Smart Citation
“…General procedure for the preparation of NSubstituted-N'-(3,S-di/I,3,S-trimethylpyrazole-4-yl)thioureas (TI-T3) The intermediate products 4-amino-3,5-dime-thyVl, 3,5-trimethylpyrazole were prepared in 4 stages from aniline or ethyl 4-aminobenzoate according to the reported procedures (19). The intermedi-ate products (0.0085 mol in 100 ml anhydrous acetone) underwent reaction with appropriate isothio-cyanate (0.0085 mol) in anhydrous acetone (100 ml).…”
Section: Chemicalsmentioning
confidence: 99%
“…However, among the numerous studies reported, there are very few concerning the metabolism of thioureas (14)(15)(16)(17)(18). We therefore investigated the in vivo metabolism of N-phenyl-N-(3,5-dimethylpyrazole-4-y1)thiourea as a potent anticonvulsant a-'Please send reprint request to: Bedia Kocyigit-Kaymakcioglu, Department of Pharmaceutical Chemistry, Faculty of Pharmacy, Marmara University, Haydarpasa, 34668, istanbul, Turkey gent (19). In this investigation, the previous results had shown that the substrate was metabolized largely unchanged form in the plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Plasma was prepared according to previously described methods [23,24]. One mL of cold acetonitrile-methanol (50:50 v/v) was added to 100 mL plasma to precipitate plasma proteins, and centrifuged at 6000 rpm for 10min.…”
Section: Preparation Of Plasma Samplesmentioning
confidence: 99%
“…Amongst this class of compounds, benzoyl derivatives of thiourea have gained a great deal of importance in the present day. Thiourea linkages have contributed greatly to the observed enhancement in various activities [3], including antiviral [4], antibacterial [5, 6], antifungal [7], antitubercular [8, 9], herbicidal [10], insecticidal [11], pharmacological properties [12], as chelating agents [13, 14] and as anticancer compounds [15]. In addition, benzoyl thiourea derivatives have often been used in analytical and biological applications [16, 17].…”
Section: Introductionmentioning
confidence: 99%